The impact of the risks of foreign currency positions on the continuity of the economic unit : Applied research (Journal of Accounting and Financial Studies ( JAFS ), 2022)
The research aims to know the extent of the impact of the risks of foreign exchange centers represented in commitment risks, liquidity risks, and exchange rate risks on the continuity of the economic unit. The research in the light of its presentation of the intellectual, cognitive and applied contributions about the risks of foreign currency centers and the continuity of the economic unit, and represented the research community in the banking sector, and the sample included nine private commercial banks listed in the Iraq Stock Exchange, and they relied on the research on a time series consisting of four years that extended from one year 2017 to 2020. The research problem was the impact of the risks associated with foreign currency centers on the continuity of the work of banks, and the research relied on financial indicators to measure the risks of foreign currency centers, and adopted the (Sherrod) model to measure the continuity of the economic unit, reinforced by the statistical methods and programs represented in the program (SPSS) to test the research hypotheses, the most important conclusions that he reached, and that non-compliance with the specified percentage according to the instructions is pure The overall currency position in relation to the capital and sound reserves may affect the continuity of the bank due to the imposition of fines on banks that exceed the ratio by the Central Bank of Iraq, and these fines are large whenever the percentage of excess is large compared to the specified ratio, and the most important recommendations reached by banks should manage Positions well and adhere to the specified percentage of the total net foreign exchange position in relation to the capital and sound reserves determined by Instruction No. (4) to facilitate the implementation of the Banking Law and the Central Bank of Iraq’s instructions because of their impact on the continuity of the bank.